PENERAPAN BAHASA PEMROGRAMAN JAVA DALAM SISTEM INFORMASI PENJUALAN VERSI DESKTOP - Windu Gata; Grace Gata (Bit (Fakultas Teknologi Informasi Universitas Budi Luhur), 2013)
At this point in each activity has many facilities that use computers to facilitate the transaction terms, so that the data obtained can be processed properly, and can generate the information needed by top management directly. It can be seen from the use of computerized systems especially for sales activity in which many business owners use a centralized sales system so that from the beginning of the transaction until the report generation can be achieved quickly and reliability in the accuracy of the data more secure. With the help of advances in information technology can create an integrated system that can assist management jobs in the business world. Information technology can help save paper in archival storage for archival storage is in the form of files that are packed in the digital media archives that can last a long time and structure. Change towards work-based computerized system that is efficient, so the competition is very tight now requires tools or systems that work easily, fast, precise, accurate, and efficient. This paper will discuss how to make the most frequently used applications for selling using the Java programming language based on the desktop. Keywords : sales information system, java programming language, system information